Bibliometric Analysis of the Publications of Law and Local Development - María Benilde Rincón-García (Revista Geon)
Problematic. The law serves as a tool for implementing public policies that support local development. However, the relationships between legal frameworks and local development is intricate and influenced by various socio-economic factors. Objectives. The study aims to assess the scientific literature concerning the role of law in local development and its impact. Materials and Methods. A bibliometric analysis was conducted using literature from 2004 to July 2024, retrieved from the Scopus database. Network analysis was applied to examine relationships between authors and identify current trends in the field. The study was complemented by multivariate statistical methods and generative probabilistic models for analysis. Results. An increase in academic production on law and local development has been observed since 2010, peaking in 2021. The network analysis reveals the existence of numerous collaboration points among institutions and authors from various countries, indicating a dynamic exchange of knowledge. Similarly, the identification of key words such as "governance", "equity", "justice" and "social participation" are important in the current academic landscape, according to the topic modeling. Discussion. The bibliometric analysis highlights patterns of interdisciplinary collaboration and emerging research themes in research in the study of law and local development. Limitations in the representation of studies exist due to reliance on databases covering specific languages and publications types. Conclusions.  Interdisciplinary collaboration is evident in research on law and local development. The findings indicate that enhancing legal frameworks can play a crucial role in promoting local development. This study provides a strong foundation for further research aiming to delve deeper into the subject. Contribution/Originality. This study offers a theoretical framework to guide future research and the development of public policies that address local needs.